UZBEKISTAN- A LAND OF RICH CULTURAL HERITAGE - Teshaboyeva Nafisa Zubaydulla qizi; Rustamova Sarvinoz O’ktamjonovna (TADQIQOTLAR, 2025)
Abstract: Uzbekistan, located at the crossroads of ancient trade routes in Central Asia, possesses a diverse and multilayered cultural heritage shaped by centuries of historical  development.  This  article  examines  the  nation’s  historical  significance, emphasizing its prominent role along the Silk Road and analyzing its architectural masterpieces,  including  Samarkand’s  Registan  Square  and  the  Historic  Centre  of Bukhara.  It  further  explores  Uzbekistan’s  vibrant  intangible  cultural  expressions—traditional craftsmanship, music, dance, oral storytelling, and cuisine—all of which continue  to  influence  national  identity.  Additionally,  the  article  considers  modern initiatives dedicated to heritage preservation, such as restoration projects, educational programs, and sustainable tourism strategies. Ultimately, Uzbekistan’s commitment to safeguarding its cultural legacy ensures that its historical narrative remains relevant and appreciated worldwide.